Economic justice in Islam : monetary justice and the way out of interest (Riba) - Hifzur Rab (A.S. Noordeen, 2006)
exiting worldviw of the economyseem to be inadequate and a humble effort has been made to analyse the problem on a broader and comperhensive perspective.